Árvores isoladas facilitam a regeneração natural em pastagem abandonada em condições de floresta estacional decidual? - Belan, Helen Carla (2015)
The natural regeneration in disturbed areas might become a slow process due to harsh conditions and constraints imposed by the environment. The positive interactions in these locations are important for the establishment of woody plant community. In abandoned pastures the isolated remnant trees facilitate regeneration by easing the environmental conditions, reducing competition below their canopies and attracting animal dispersers that might increase the local seed rain. Thus, this study aimed to understand the role of isolated trees in the regeneration process and evaluate which factors might affect this process. For this purpose, we selected an abandoned pasture in Deciduous Seasonal Forest conditions (DSF), located within the borders of Parque Estadual do Pau Furado (Pau Furado State Park), Uberlândia MG. In a 10 - hectare area we selected twenty isolated trees and set four 4m² - plots in each one, two below the canopy and two outside the canopy (open area). All the regenerating woody individuals found in the plots were measured and identified. Some characteristics of the trees were also measured: tree height, canopy coverage and area, and distance from the nearest DSF fragment. The environmental data of temperature and relative humidity were gathered in both environments (below and outside the canopy) in two distinct seasons (dry and rainy). The natural regeneration was represented by 245 woody individuals (224 in the plots below the canopy and 21 in the plots outside the canopy), distributed in 51 species, 42 genera, and 22 botany families. The most important families were Fabaceae, Myrtaceae, Rubiaceae, Malvaceae and Bignoniaceae. The plots below the canopy showed higher density of individuals and species richness when compared to the plots outside the canopy. When it comes to dispersion syndrome, the zoochore species were predominant (46.9%), indicating that isolated trees attract dispersers that deposit the seeds on site. As a direct effect of canopy shading we recorded lower temperature and higher values of relative humidity below the canopy in both seasons. The shading also affected the grass coverage that was reduced below the canopy. This reduction is important for seedlings establishment and growing, since alien grasses set limits to natural regeneration due to competition. From the analyzed environmental and biophysical factors by using Canonical Correspondence Analysis (CCA), the height, the canopy area and RH showed a relation to distribution of woody species. The relation species/environment was significant in the dry season (p<0.05), according to Monte Carlo test even though it only explained 23.7 of data variation. In stressful environments, as abandoned pastures, a successful regeneration will probably rely on the existence of isolated trees that act as facilitators easing, thus, the environmental conditions below their canopies.